Accuracy of chest X-Ray measurements of pediatric esophageal coins. (October 2018) - Huyett, Phillip; Shaffer, Amber; Flom, Linda; Simons, Jeffrey P.; Jabbour, Noel
Abstract: Objective: To determine the accuracy of chest x-ray measurements in children using ingested radiopaque foreign bodies of known size. Methods: A database of foreign body ingestions at a tertiary care children's hospital was queried from 2013 to 2016 for children who had ingested a US coin, had a pre-operative chest x-ray and documentation of coin type at the time of endoscopic removal. Four blinded research subjects measured the coin diameter on chest x-ray using iSite PACS software and based on the measurement, predicted the coin type. Measurements were compared to the known coin diameters published by the US Mint. Results: A total of 51 patients with sixteen esophageal quarters (diameter 24.26 mm), fourteen nickels (21.21 mm), fourteen pennies (19.05 mm) and seven dimes (17.91 mm) were included in the study. The four subjects had a mean accuracy of 60.3% (range 49.0%–72.5%) in predicting the correct coin type. Across all raters, there was poor agreement for pennies (kappa = 0.161) and dimes (kappa = 0.131), fair agreement for nickels (kappa = 0.259), good agreement for quarters (kappa = 0.687), and fair agreement overall (kappa = 0.371). The study measurements overestimated the coin size in 203 of the 204 measurements by a mean of 1.84 mm (range −0.31–3.85 mm). The mean size discrepancy was larger (2.40 vs. 1.30 mm, p < 0.001) and accuracy of coin type identification was worse (44.6% vs. 74.1%, p = 0.001) in children <4 years old. Conclusions: Measurement of esophageal coins on chest x-ray is relatively inaccurate and overestimates the size in the majority of cases. Clinicians should use caution when performing fine measurements on chest x-rays, especially in children younger than 4 years old.